Right Ventricular Systolic and Diastolic Function Profile inPatient with Stable Chronic Obstructive Pulmonary Disease - Oktavia, Dina; Nasution, Sally Aman; ZN, Anna Uyainah; Rumende, C Martin (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Right ventricular dysfunction is one of the common complication of chronic obstructive pulmonary disease (COPD). Right ventricular assessment is importance, since it related with exercise intolerance and poor prognosis. Methods. Thirty stable COPD men (mean age: 65 ± 6 yr) underwent spirometry. In addition to conventional echocardiographic parameters, TAPSE, right heart chambers, and trans tricuspid inflow were determined. Results. The mean value of FEV1 was 28 ± 8% of the predicted value. There was no subject with mild airflow limitation, 57% subjects were with very severe airflow obstruction. All of pulmonary function test showed mixed restrictive-obstructive pattern. Mean of right chamber was in normal limit. Forty percent of the patients suffered right ventricular diastolic dysfunction. Means of TAPSE was 16.96 ± 96 mm. Sixty percent of the patients suffered right ventricular systolic dysfunction. There was no significant difference in TAPSE between groups with moderate-severe flow obstruction and very severe airflow obstruction. There was no significant correlation between FEV1 % prediction and TAPSE, so the cut-off value between the two variables cannot be determined. Conclusions. The proportion of right ventricular systolic dysfunction was 60% and diastolic dysfunction was 40%. There was no correlation between FEV1 % prediction and TAPSE. The cut-off value between the two variable in stable COPD patients cannot be determined.